Về khoáng vật chỉ thị của Kimberlit và Lamproit ở Việt Nam - Phượng, Ngô Thị; Hòa, Trần Trọng; Anh, Trần Tuấn; Afanaxev, V. P. (Vietnam Journal of Earth Sciences, 2001)
About indicator mineral of Lamproites and Kimberlites in Vietnam